THE FINANCE CRISIS IN EUROPE AND POSSIBLE REMEDIES: PROBLEMS OF EU LAW AND CONSTITUTIONAL LAW - Arnold, RAINER (Anales Universitatis Apulensis Series Jurisprudentia, 2013)
Economic and financial crises are embedded into the global, regional and national political and legal context. The expansion of economics and the transnational nature of politics are the reasons for the internationalization of crises. Multinational cooperation systems work under specific transnational conditions and, if they fail, their failure has transnational effects. Globalization corresponds to the requirements of contemporary task performance but globalizes also the crises. The instruments to face such international or regional–transnational crises have necessarily to be adapted their very nature; national remedies do not seem to be sufficient, they must be complementary to multinational instruments. Keywords: Economic crises, financial crises, transnational nature of politics, internationalization of crises